Manganese (Mn) and Zinc (Zn) for Citrus Trees - Mongi Zekri; Tom Obreza (EDIS)
Since mineral nutrition is a major factor in maximizing yield of high-quality fruit, understanding the functions of mineral elements, diagnosing nutrient deficiencies, and providing needed fertilizers are essential. This publication describes and discusses manganese (Mn) and zinc (Zn) deficiencies, functions, and recommended practices to alleviate nutritional problems. This 5-page fact sheet was written by Mongi Zekri and Tom Obreza , and published by the UF Department of Soil and Water Science, March 2014.